Investigasi Peran Kepuasan Dalam Penciptaan Loyalitas Wisatawan Di Klenteng Sam Poo Kong Kota Semarang - Aprih Santoso; Emaya Kurniawati (Badan Riset dan Inovasi Daerah Kota Semarang, 2025)
The purpose of this study was to examine the role of satisfaction in mediating the influence of trust and service quality on loyalty in creating tourist loyalty at Sam Poo Kong Temple in Semarang City. The method used in this study is quantitative. Based on calculations using the Slovin formula, the sample of this study was 100 respondents. The results of the study showed that partially and simultaneously there was a positive and significant influence of trust and service quality on tourist satisfaction and loyalty at Sam Poo Kong Temple in Semarang City. Satisfaction has a positive and significant effect on tourist loyalty at Sam Poo Kong Temple in Semarang City. Satisfaction is able to mediate the influence of trust and service quality on tourist loyalty at Sam Poo Kong Temple in Semarang City.